Safety Culture in Intensive Care Units from Multiprofessional Team Perspective: A Multicenter Study - Pequeno Andrade Rasslan Silva, Bárbara (2025)
Introduction: Patient safety culture is considered an important structural component of the services, which promotes the implementation of safe practices and the reduction of adverse events. Objective: To identify the factors associated with patient safety culture in adult intensive care units in large hospitals in Belo Horizonte. Method: Cross-sectional survey and multicenter study. A total of 168 health professionals from four units (A, B, C and D) of adult intensive care participated. The questionnaire “Hospital Survey on Patient Safety Culture” was used. The patient's level of safety culture was considered as a dependent variable, and sociodemographic and labor aspects were the independent variables. Descriptive statistics were used and a multiple logistic regression model was developed to analyze the associated factors. Results: An association was identified between the type of hospital and eleven dimensions of the safety culture. In terms of function, the doctors, nursing technicians, and nurse were related to three dimensions; gender with two dimensions, and time working in the sector with one dimension. Conclusion: It was evidenced that the type of hospital, function, time working in the sector, and gender were associated with the dimensions of patient safety culture.